The Fractal property of cartographic lines: a study case of the coast l ine of São Paulo State - Brazil - Thiago Salomão de Azevedo (GEOUSP: Espaço e Tempo, 2004)
This paper presents a study case involving the influence of resolution on estimative of the Fractal Dimension (D) of the São Paulo State coastline. To analyze such influence we calculate D for two coastal zones. One was located in Maresias, north coastal zone, and the other in Itanhaém, south coastal zone. The results showed that the resolution altered the fractal estimative of coastal shoreline. However, the results also indicate that this influence is smaller in Itanhaém compared with that in Maresias